Mosaicos da memória: estudo da crônica humorística de Luís Fernando Veríssimo - Antonio, Andréia Simoni Luiz [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
This study intends to present an analyses of Luís Fernando Veríssimo s chronicles. The chronicles are published on 80s and 90s and they can be find on the books: O popular, 1973; A grande mulher nua, 1975; Amor brasileiro, 1977; O rei do rock, 1978; Sexo na cabeça, 1980; O analista de Bagé, 1981; Outras do analista de Bagé, 1982; A velhinha de Taubaté, 1983; A mulher do Silva, 1984 e A mãe do Freud, 1985. The general mains of this study are: to study the origin and the development of the chronicle in Brazil and to understand, on Luís Fernando Veríssimo s productions, the relations among his literature, the History and the newspaper. First of all, this work situates the representative moments of the chronicles s story, its origin, the influence of the newspaper (since times of the folhetim). After this, the study searches for the corpus s analyse, specifically, for the study of the relations between humour and chronicle and about the comic resources used in Luís Fernando Veríssimo s chronicles. The methodology used in this analyses results in the models. These models show the main thematic and structural characteristic of the corpus, and they are divided into: crônicas metalingüísticas, crônicas meta-humorísticas, crônicas politico-sociais, crônicas de costumes e crônicas lingüísticas or crônicas de/sobre palavras. The relation between text and context was stablished in this work, in other words, each chronicle sends, at least, an aspect of the cultural and social context on 1970 and 1980. This contest is retaken and it used to improve the literary interpretation of the ficcional text, because, in the chronicle, the external element leaves of being only a social and political description to becoming an internal element of the literature... (Complete abstract, click electronic access below)
Keywords: Veríssimo, Luis Fernando, 1936- - Crítica e interpretação; Cronicas brasileiras; Humorismo